Renin–angiotensin–aldosterone pathway modulators in chronic kidney disease: A comparative review - Alshahrani, Saeed (Frontiers in Pharmacology, 2023)
Chronic kidney disease presents a health challenge that has a complex underlying pathophysiology, both acquired and inherited. The pharmacotherapeutic treatment options available today lower the progression of the disease and improve the quality of the life but cannot completely cure it. This poses a challenge to the health care provider to choose from the available options the best to manage the disease as per the presentation of the patient. As of now the recommended first line of treatment to control the blood pressure in chronic kidney disease is the administration of renin-angiotensin-aldosterone system modulators. There are represented mainly by the direct renin inhibitor, angiotensin-converting enzyme inhibitors, and angiotensin II receptor blockers. These modulators are varied in their structure and mechanisms of action, hence having varying treatment outcomes. The choice of administration of these modulators is determined by the presentation and the co-morbidities of the patient, the availability and affordability of the treatment option, and the expertise of the health care provider. A direct head-to-head comparison between these significant renin angiotensin aldosterone system modulators is lacking, which can benefit healthcare providers and researchers. In this review, a comparison has been drawn between the direct renin inhibitor (aliskiren), angiotensin-converting enzyme inhibitors, and angiotensin II receptor blockers. This can be of significance for the health care providers, as well as the researchers to find the particular loci of interest, either in structure or mechanism, to intervene as per the case presentation to obtain the best possible treatment option.